Beyond Conditionality: China's New Path in Foreign Aid and Sovereign Lending - Qifang Deng (Lecture Notes in Education Psychology and Public Media, 2026)
Western-dominated development lending, led by the IMF and Paris Club, has long relied on rigid policy conditionality and structural adjustment packages that frequently deepen inequality in low-income recipient states. Since 2017, commentators and Western politicians have popularized the so-called "Chinese debt trap" narrative, claiming China deliberately saddles poorer nations with unsustainable liabilities to seize strategic infrastructure amid repayment defaults. Focusing on the most widely cited case—the Hambantota Port in Sri Lanka—this study dismantles such one-sided claims through primary project timelines and sovereign debt data. Evidence from this paper demonstrates the port initiative originated from Sri Lanka's domestic infrastructure demands rather than Chinese coercion; loan pricing remained competitive against global commercial financing at the time, and the 99-year port lease constituted a stand-alone commercial transaction to ease the nation's liquidity squeeze, not a debt-for-asset seizure. Overall, this paper argues that China's non-conditional bilateral lending represents an alternative development finance model distinct from Western orthodox approaches, while oversimplified debt-trap rhetoric conceals the complex structural drivers of developing nations' external debt pressures.